Overeducation In The Labour Market - Gabriela Wronowska (Institute of Economic Research (IER), 2017)
During the transition period in Poland, its labour market changed dynamically. Many new phenomena which the Polish economy had never seen before manifested themselves. The society showed greater interest in higher education and the market for education services expanded, increasing the number of colleges and universities, especially private ones. This helped the spread of higher education, which for years determined the level of human capital represented by the supply of labour. Today's labour market in Poland is showing signs of imbalance. One of the reasons involves overeducation. The phenomenon has been known since the 1970s. It was then described for the first time in pertinent literature, with the US where overeducation occurred on a large scale and where it had a number of adverse effects across the entire economy having been used as an example. It seems important to understand and analyse the reasons for the emergence and perpetuation of this phenomenon on the Polish labour market and to indicate its implication. The paper aims to present and discuss overeducation in terms of selected economic theories, identify its causes in Poland and further to determine the economic and social implications of the persistence of the phenomenon in the long run. The paper consists of a theoretical part developed based on selected Polish and English-language literature. The empirical material used in the paper comes from latent data originating in domestic and EU statistical databases, and is further partly sourced out from the author's own research, and data collected by other researchers. Based on the author's analysis, it can be concluded that overeducation is a complex phenomenon. It is possible to identify several reasons for its occurrence and long-drawn persistence on the Polish labour market. Some of the reasons have to do with the dynamic growth of the labour market and the educational services sector, society's desire to gain higher education, structural mismatches in the labour market and a common education policy at the EU level. Overedutaion has far-reaching consequences, both for the entire economy and the single participant of the labour market alike. The fact of its occurrence determines the processes taking place in the labour market, especially those related to employment.
Keywords: A11; A14; 330; labour market; overeducation; human capital